2011
DOI: 10.1111/j.1467-8551.2011.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formal Contracts, Relational Norms and Trust on Performance of Joint Research and Development Projects

Abstract: This paper examines the effect of governance mechanisms -formal contracts, relational norms and trust -on the performance of exploration and exploitation joint research and development (R&D) projects. While the authors acknowledge the need for a twofold approach, transactional and relational, to understand the interfirm exchange governance, the joint action of formal contracts and relational governance has been caught between the complementary or substitutive forces involved in interorganizational relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 77 publications
8
112
0
3
Order By: Relevance
“…This is similar to previous studies, which show that transactional and relational governance complement each other (Arranz & de Arroyabe 2012;Blomqvist, et al 2005;Gulati 1995;. Much of the relational governance took place within the R&D project team and involved the project manager, especially in the projects with high technological uncertainty.…”
Section: Organizational Separation and Complementaritysupporting
confidence: 75%
See 3 more Smart Citations
“…This is similar to previous studies, which show that transactional and relational governance complement each other (Arranz & de Arroyabe 2012;Blomqvist, et al 2005;Gulati 1995;. Much of the relational governance took place within the R&D project team and involved the project manager, especially in the projects with high technological uncertainty.…”
Section: Organizational Separation and Complementaritysupporting
confidence: 75%
“…Yet, the risks related to information asymmetry (when the supplier knows more than the customer), asset obsolescence (when specific investments are made), and switching costs to shift business to alternative suppliers are high (Mahapatra, et al 2010). In these situations, the role of relational governance as a complement and/or substitute for transactional governance increases (Arranz and de Arroyabe 2012;Cannon, et al 2000;Zhou, et al 2008). Consequently, previous research has shown that transactional and relational governance mechanisms are applied simultaneously.…”
Section: Transactional and Relational Governancementioning
confidence: 99%
See 2 more Smart Citations
“…Cattani and Ferriani 2008;Cross and Cummings 2004). Furthermore, those with high JE have been exposed to a broader array of concepts, developmental processes, and collaborative styles (Arranz and Fdez de Arroyabe 2012). A crew with more diverse experiences may also offer greater novelty and breadth in their abilities to apply unconventional ideas, leading to competitive advantages (Cattani and Ferriani 2008).…”
Section: Impact Of Pe and Je By Functional Role And Studio As A Modermentioning
confidence: 99%